Quality of Life of Youths with and without Disabilities: A Comparative Study - Rohana, Jani; Alias, Abd Aziz; Nur Fatihah, Abdullah Bandar (UPM, 2017)
Introduction: The objective of this paper is to compare the self-perceived Quality of Life (QOL) of youths with and without disabilities using WHOQOL-BREF instrument.